Clinical cases in obstetrics, gynaecology, and women's health - De Costa, Caroline 1947; Robson, Stephen; Lim, Boon (Clinical cases series, 2013)
Clinical Cases in Obstetrics, Gynaecology and Women's Health" presents realistic short and long case studies across a diverse range of clinical settings. Each case is followed through its various stages and offers a number of logical and practical ways of investigating and managing the presenting condition. In addition, the case studies are supplemented with guidelines/clinical tips, chapter objectives, lists of key points, tables, test results and references